Determining the level of welfare among foreign workers: a case study in Melaka - Ali, Asrizal (2004)
This study is interested to study on the level of welfare enjoyed and provided to the foreign workers in Melaka. Besides that, this study also examines the level of satisfaction among foreign workers towards their welfare. Welfare is important to the foreign workers whom are away from their family and home country. They need a basic facility such as food, and accommodation in order to live in their new home. They also experienced cross culture diversity, which there is a different in language, food, culture and etc. However, because of their status, many employers are taking such advantages by discriminate them for their own interest and profit. The problems of these workers also include abuse of their right to freedom of movement. Apart from all these problems, most of the foreign workers face wage discrimination, non-payment, and poor living and working conditions. They are also deprived of many facilities promised to them by their agents. The lack of legal regime back home, and no legal aid in the largely unknown country, makes them vulnerable in all situations.